2007
DOI: 10.4103/0253-7613.30756
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crude aqueous leaf extract of Viscum album (mistletoe) in hypertensive rats

Abstract: d o w n l o a d f r o m a s i t e h o s t e d b y M e d k n o w P u b l i c a t i o n s (w w w. m e d k n o w. c o m) .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…(33585/HNC)/EuphorbiaceaeInfertility, menstrual pain, dysentery, typhoid fever [12]Leaves, whole plantProstratins A, B and C, rugosins A, D, E and G, quercetin 3- O -β-sambubioside, euphorbins G and H, tellimagradin I and II, kaempferol, cosmosiin, rhamnetin-3-galactoside, quercetin, β-amyrine acetate, β-sitosterol, campesterol, stigmasterol and cholesterol [26, 27]Antibacterial, antifungal, bleeding haemorrhoids [12, 28, 29] Markhamia tomentosa K. Schum. (1974/SRF-Cam)/BignoniaceaeEdema, cancer, gout, scrotal elephantiasis, pulmonary troubles, general body pain [30]Leavesβ-sitosterol, β-sitosterol-3- O -β- d -glucopyranoside, dehydroiso-α-lapachone, 2-acetylnaphtho[2,3-b]furan-4,9-dione, pomolic acid, 2-acetyl-6-methoxynaphtho[2,3-b]furan-4,9-dione, β-lapachone, tormentic acid, oleanolic acid, palustrine [31, 32]Antiprotozoal, antihelmintic, antibacterial, antifungal, antiviral, analgesic, anti-inflammatory antioxidant, anti-tumor [3133] Viscum album L. (2974/HNC)/LoranthaceaeAtherosclerosis, hypertension, cancer, headache, dizziness, palpitation [34, 35]LeavesConiferin, syringin, eleutheroside E, syringaresinol- O -glucoside, ligalbumosides A–E, alangilignoside C, kalopanaxin D, β-amyrin acetate, β-amyrin, lupeol, lupeol acetate oleanolic acid, betulinic acid, stigmasterol, β-sitosterol, trans -α-bergamotene, trans -β-farnesene, loliolide, vomifoliol, 5,7-dimethoxy-flavanone-4′- O -glucoside, 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -glucoside, 5,7-dimethoxyflavanone-4′- O -[2′′- O -(5′′′- O - trans -cinnamoyl)-apiosyl]-glucoside), 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -[2′′- O -(5′′′- O - trans -cinnamoyl)-apiosyl]-glucoside, 2′-hydroxy-3,4′,6′-trimethoxychalcone-4- O -glucoside, 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -[apiosyl(1 → 2)]-glucoside, 5,7-dimethoxyflavanone-4′- O -[apiosyl-(1 → 2)]-glucoside, (2 S )-3′,5,7-trimethoxyflavanone-4′- O -glucoside, 4′- O -[β-apiosyl(1 → 2)]-β-glucosyl]-5-hydroxy-7- O -sinapylflavanone, 3-(4-acetoxy-3,5-dimethoxy)-phenyl-2 E -propenyl-β-glucoside, 3-(4-hydroxy-3,5-dimethoxy)-phenyl-2 E -propenyl-β-glucoside, 4′,5-dimethoxy-7-hydroxy flavanone, 5,7-dimethoxy-4′-hydroxy flavanone [36]Antihypertensive, cytotoxicity, vascular effects, antioxidant, antibacterial [34, 35, 37, 38] Rauwolfia macrophylla Ruiz & Pav. (1697/SRFK)/ApocynaceaeMeasles or itching rash, fever, swellings, rheumatism, hepatitis, pneumonia, abdominal pain, cough and toothache, headache, insomnia and palpitation of the heart, abscess, roundworm, tapeworm, hypertension, epilepsy, eye diseases, venereal diseases [39]Leaves, bark, roots…”
Section: Methodsmentioning
confidence: 99%
“…(33585/HNC)/EuphorbiaceaeInfertility, menstrual pain, dysentery, typhoid fever [12]Leaves, whole plantProstratins A, B and C, rugosins A, D, E and G, quercetin 3- O -β-sambubioside, euphorbins G and H, tellimagradin I and II, kaempferol, cosmosiin, rhamnetin-3-galactoside, quercetin, β-amyrine acetate, β-sitosterol, campesterol, stigmasterol and cholesterol [26, 27]Antibacterial, antifungal, bleeding haemorrhoids [12, 28, 29] Markhamia tomentosa K. Schum. (1974/SRF-Cam)/BignoniaceaeEdema, cancer, gout, scrotal elephantiasis, pulmonary troubles, general body pain [30]Leavesβ-sitosterol, β-sitosterol-3- O -β- d -glucopyranoside, dehydroiso-α-lapachone, 2-acetylnaphtho[2,3-b]furan-4,9-dione, pomolic acid, 2-acetyl-6-methoxynaphtho[2,3-b]furan-4,9-dione, β-lapachone, tormentic acid, oleanolic acid, palustrine [31, 32]Antiprotozoal, antihelmintic, antibacterial, antifungal, antiviral, analgesic, anti-inflammatory antioxidant, anti-tumor [3133] Viscum album L. (2974/HNC)/LoranthaceaeAtherosclerosis, hypertension, cancer, headache, dizziness, palpitation [34, 35]LeavesConiferin, syringin, eleutheroside E, syringaresinol- O -glucoside, ligalbumosides A–E, alangilignoside C, kalopanaxin D, β-amyrin acetate, β-amyrin, lupeol, lupeol acetate oleanolic acid, betulinic acid, stigmasterol, β-sitosterol, trans -α-bergamotene, trans -β-farnesene, loliolide, vomifoliol, 5,7-dimethoxy-flavanone-4′- O -glucoside, 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -glucoside, 5,7-dimethoxyflavanone-4′- O -[2′′- O -(5′′′- O - trans -cinnamoyl)-apiosyl]-glucoside), 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -[2′′- O -(5′′′- O - trans -cinnamoyl)-apiosyl]-glucoside, 2′-hydroxy-3,4′,6′-trimethoxychalcone-4- O -glucoside, 2′-hydroxy-4′,6′-dimethoxychalcone-4- O -[apiosyl(1 → 2)]-glucoside, 5,7-dimethoxyflavanone-4′- O -[apiosyl-(1 → 2)]-glucoside, (2 S )-3′,5,7-trimethoxyflavanone-4′- O -glucoside, 4′- O -[β-apiosyl(1 → 2)]-β-glucosyl]-5-hydroxy-7- O -sinapylflavanone, 3-(4-acetoxy-3,5-dimethoxy)-phenyl-2 E -propenyl-β-glucoside, 3-(4-hydroxy-3,5-dimethoxy)-phenyl-2 E -propenyl-β-glucoside, 4′,5-dimethoxy-7-hydroxy flavanone, 5,7-dimethoxy-4′-hydroxy flavanone [36]Antihypertensive, cytotoxicity, vascular effects, antioxidant, antibacterial [34, 35, 37, 38] Rauwolfia macrophylla Ruiz & Pav. (1697/SRFK)/ApocynaceaeMeasles or itching rash, fever, swellings, rheumatism, hepatitis, pneumonia, abdominal pain, cough and toothache, headache, insomnia and palpitation of the heart, abscess, roundworm, tapeworm, hypertension, epilepsy, eye diseases, venereal diseases [39]Leaves, bark, roots…”
Section: Methodsmentioning
confidence: 99%
“…The aqueous extract also brought on a significant decrease in blood pressure, which was higher in hypertensive than in normotensive animals. The research method applied permits to suppose that the activity of the extract occurs mainly through the favourable reaction of the nervous system and its influence on peripheral blood vessels (Ofem et al 2007).…”
Section: Antihypertensive Activitymentioning
confidence: 99%
“…2). Ofem et al (2007) suggested that the reduction in blood pressure without any alteration in heart rate by aqueous extract of leaves of Viscum album L. growing on citrus may be due to catecholamine-like blocking agent(s), showing predominantly alpha-1 adrenoceptor antagonist action or agonist-like agents that may be stimulating the beta-2 adrenoceptors to produce the depressor effect. In turn, Radenkovic et al (2009) proposed that decreases in the blood pressure in rats treated with ethanolic extracts of Viscum album L. steams might be connected with muscarine cholinergic receptors.…”
Section: Cardiac Activitymentioning
confidence: 99%